Posttraumatic Cholesteatoma Complicated by a Facial Paralysis: A Case Report - M. Chihani; A. Aljalil; M. Touati; B. Bouaity; H. Ammar (Case Reports in Otolaryngology)
The posttraumatic cholesteatoma is a rare complication of different types of the temporal bone damage. Its diagnosis is often done after several years of evolution, sometimes even at the stage of complications. A case of posttraumatic cholesteatoma is presented that was revealed by a facial nerve paralysis 23 years after a crash of the external auditory canal underlining the importance of the otoscopic and radiological regular monitoring of the patients with a traumatism of the temporal bone.